2016
DOI: 10.1016/j.celrep.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Genomics-Based Taxonomy of Renal Cell Carcinoma

Abstract: Summary On the basis of multidimensional and comprehensive molecular characterization (including DNA methylation and copy number, and RNA and protein expression), we classified 894 renal cell carcinomas (RCCs) of various histologic types into nine major genomic subtypes. Site of origin within the nephron was one major determinant in the classification, reflecting differences between clear cell, chromophobe, and papillary RCC. Widespread molecular changes associated with chromatin modifier genes or TFE3 gene fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
340
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(373 citation statements)
references
References 36 publications
26
340
1
2
Order By: Relevance
“…Interestingly, specific kidney cancer susceptibility loci may differ in the black population [24]. Future casecontrol studies evaluating kidney cancer susceptibility should focus on specific histologic subtypes, as the genomic basis of each differs greatly [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, specific kidney cancer susceptibility loci may differ in the black population [24]. Future casecontrol studies evaluating kidney cancer susceptibility should focus on specific histologic subtypes, as the genomic basis of each differs greatly [25].…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the association between transcript levels and DNA methylation at corresponding CpG islands, coordinated changes were detected in chromosome 19q13 genes ( Figure 6B and Supplemental Table 7). Notably, the downregulation of 19q23 genes was shown to associate with SETD2 mutations in clear or papillary kidney cancers (20), whereas SETD2 mutation was not detected in chRCC (Supplemental Table 3 …”
Section: Wgs On 5 M-hrcc Cases Identifies Recurrent Genomic Aberrationsmentioning
confidence: 99%
“…Conventional cytogenetic studies have demonstrated classical loss of a nonrandom set of 7 chromosomes, i.e., 1, 2, 6, 10, 13, 17, and 21, in most chRCC (termed chRCC-7set hereafter) (5,18), resulting in lower overall ploidy compared with other human cancers (19,20). Recent genomic analyses of 2 chRCC cohorts of 66 and 49 cases using contemporary platforms, encompassing whole-genome sequencing (WGS), whole-exome Chromophobe renal cell carcinoma (chRCC) typically shows ~7 chromosome losses (1, 2, 6, 10, 13, 17, and 21) and ~31 exonic somatic mutations, yet carries ~5%-10% metastatic incidence.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA repair defects thus drive genomic instability and dysregulate tumor microenvironment [32]. loss has been shown to define a distinct molecular subtype of clear cell renal cell carcinoma (ccRCC) and UM [33][34][35]. These studies showed that, similar to BAP1 del PeM subtype, BAP1 del tumors from both ccRCC and UM also have dysregulated chromatin modifiers, impaired DNA repair pathway, and immune checkpoint receptor activation.…”
Section: Discussionmentioning
confidence: 99%